ECAI 2006 17th European Conference on Artificial Intelligence, August 29-September 1, 2006, Riva del Garda, Italy : including Prestigious Applications of Intelligent Systems (PAIS 2006) : proceedings - Brewka, Gerhard 1955-; Cordeschi, Silvia; Perini, Anna; Traverso, Paolo (IOS Press, 2006)
In the summer of 1956, John McCarthy organized the famous Dartmouth Conference which is commonly viewed as the founding event for the field of Artificial Intelligence. Knowledge Representation & Reasoning is traditionally strong in Europe and remains the biggest area of ECAI 2006
Includes bibliographical references. - Description based on print version record
Open Access
Keywords: Künstliche Intelligenz; Artificial intelligence / Congresses; COMPUTERS; Enterprise Applications; Business Intelligence Tools; COMPUTERS; Intelligence (AI) & Semantics; Conference papers and proceedings; Artificial intelligence; Electronic books; Electronic books / Conference proceedings; Konferenzschrift